Working conditions and satisfaction with working conditions among Slovenian family medicine trainees: A cross-sectional study - Pašić Klemen; Ivetić Vojislav (Sciendo, 2021)
In order to achieve a high standard in training programmes for future family medicine specialists, it is essential to have good tutors with well-organised family medicine practices. Proper working conditions for young doctors are essential for their satisfaction and future professional development. The aim of our study was to check the current working conditions of family medicine trainees in the practical modular part of the training programme in Slovenia, and to determine their satisfaction with working conditions.